INTELLECTUAL CAPITAL DISCLOSURE AND COMPANY PERFORMANCE: A COMPARISON STUDY OF SHARIA BANK IN INDONESIA AND MALAYSIA - Azeeta Nur Partiwi; Puji Handayati; Nurika Restuningdiah (Yayasan Education and Social Center, 2022)
This study aimed to compare the performance of Islamic banking companies in Indonesia and Malaysia in terms of intellectual capital disclosure (ICD). ICD is measured using Ulum's Indonesian Intellectual Capital Disclosure (ICD-In) framework (2015). IC is divided into three categories and 36 items: human capital (8 items), structural capital (15 items), and relational capital (13 items). Meanwhile, the company's performance variable is measured by using profitability ratios, namely, return on assets (ROA) and return on equity (ROE), and Capital Adequacy Ratio (CAR). The population in this study are Islamic banking companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange from 2017 to 2020. The sample in this study amounted to 16, consisting of 8 Indonesian Islamic banks and 8 Malaysian Islamic banks. This study makes use of secondary data from the company's annual reports. This study used content analysis and a T-test as analytical tools. According to the findings, the ICD component, namely the relational capital of Malaysian Islamic banks, is lower than that of Indonesian Islamic banks. As for the company performance variable, the results of the research show that the ROA of Malaysian Islamic banks is higher than that of Indonesian Islamic banks, the ROE of Malaysian Islamic banks is higher than that of Indonesian Islamic banks, and the CAR of Malaysian Islamic banks is lower than that of Indonesian Islamic banks.